Evaluation of the Factor Structure of the Obstacles to Engagement Scale with Low-Income African American Parents - Davis, Deborah Winders; Dempster, Robert; Myers, John A.; Jones, Veronnie Faye; Ryan, Lesa; Logsdon, M. Cynthia (Frontiers in Pediatrics, 2014)
Objective: Parenting anticipatory guidance is one way to promote optimal child health and development and minimize disparities between children from lower socio-economic status families and their higher income peers. However, low rates of attendance at and completion of parenting programs has been demonstrated. Understanding barriers to participation has important implications. The Obstacles to Engagement Scale (OES) has been used in some populations, but it has not been evaluated for use with low-income African American samples. The aim of the current study is to evaluate the factor structure of the OES with a sample of low-income, African American parents. Method: Parents or legal guardians with children aged 3-8 years completed a survey in the waiting room of a primary care pediatric academic practice in an urban location in the southern United States of America (N = 114). Almost 87% had < 12th grade education and 93% of the children received Medicaid services. The OES was one measure from a larger study and only participants with complete data on the OES were included in the exploratory factor analysis (EFA). Results: The EFA did not support the previous 4-factor solution (intervention demands, personal or family stressors or obstacles, relevance of or trust in intervention, and time and scheduling demands. Instead, a 3-factor statistical solution emerged, but not all items held together conceptually. Conclusions: The current study supports the necessity for evaluating study instruments for use with specific populations. Larger samples are needed to disentangle the effects of educational and poverty status from race and ethnicity and to develop and validate instruments that are appropriate for the study population.